Effect of Water Extraction on Phytochemicals and Antioxidant Activities of Red Algae (Caloglossa beccarii De Toni) - Luealae, Wanlapa; Penprapai, Pensri; Chankaew, Wanninee (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The objectives of this research were to compare the phytochemical contents and antioxidant activities analyzed by scavenging activity of ABTS radical and metal ablating activity of Caloglossa beccarii aqueous extract using 5 different extraction conditions (4 oC/24 h, 25 oC/12 h, 50 oC/6 h, 75 oC/3 h and 100 oC/1.5 h). Caloglossa beccarii, was collected from Nakhon Si Thammarat province. The results showed the total phenolic compound, total flavonoid content and antioxidant activities content were significantly different among extract condition (p < 0.05). The aqueous extract at 25 oC/12 h showed the highest of total phenolic compound was 32.95±0.21 mgGAE/g extract and the best activity of scavenging ABTS with IC50 = 0.24±0.00 mg/mL, respectively. The extract at condition 4 oC/24 h showed the highest of total flavonoid was 24.67±0.04 mgQE/g extract and the lowest IC50 with metal chelation = 0.27±0.00 mg/mL, respectively. This findings indicated that the aqueous extracts at condition 4 oC/24 h and 25 oC/12 h were the most suitable for antioxidant extraction from C. beccarii.